Can simvastatin improve erectile function and health‐related quality of life in men aged ≥40 years with erectile dysfunction? Results of the Erectile Dysfunction and Statins Trial [ISRCTN66772971]. (11th June 2012) - Trivedi, Daksha; Kirby, Michael; Wellsted, David M.; Ali, Shehzad; Hackett, Geoffrey; O'Connor, Bernadette; van, Sandra
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? Erectile dysfunction (ED) is often associated with endothelial dysfunction. It is also recognized as a marker for underlying vascular disease. There are missed opportunities to address cardiovascular risk factors in these men. Simvastatin administered for 6 months improves sexual health‐related quality of life in men aged ≥40 years with untreated ED. It reduces the risk of future cardiovascular events via a reduction in serum cholesterol in men with ED. A non‐significant trend towards improving erectile function suggests longer trials with a more potent statin may be required. There is high probability (>80%) of simvastatin being cost‐effective in men with ED. Enquiry about erectile function provides the opportunity to address cardiovascular risk factors. Objective To evaluate the effectiveness and cost‐effectiveness of simvastatin on erectile function and health‐related quality of life in men aged ≥40 years with erectile dysfunction (ED). Patients and Methods ED is common in men aged ≥40 years and impacts upon their overall health‐related quality of life and that of their partners. Men aged ≥40 years who were not receiving lipid lowering or anti‐hypertensive medication and not at high cardiovascular risk were recruited from 10 general practices in the East of England. In total, 173 eligible men with untreated ED were randomized to double‐blind treatment with 40 mg of simvastatin or placebo once daily for 6 months. Data were collected at three points over 30 weeks. The main outcome was erectile function (International Index of Erectile Function‐5 score). Secondary outcomes included male ED‐specific quality of life (MED‐QoL), quality‐adjusted life years (QALYs) using the generic Euroqol measure (EQ‐5D), endothelial function, cardiovascular risk, cholesterol and health service costs. Results There was no significant difference in erectile function between the simvastatin and placebo groups (mean change, 1.28 vs 0.07, z = 1.1, p = 0.27), although a significant improvement in MED‐QoL was observed (5% vs 2%, z = 2.09, p = 0.04). Both 10‐year cardiovascular risk and low‐density lipoprotein were reduced (cardiovascular risk, z = −3.67, p < 0.001; low‐density lipoprotein, z = −5.46, p < 0.001), with no consistent change in endothelial function. The frequency of sexual encounters is correlated with improved erectile function. The joint distribution of costs and QALY benefits indicates that the probability of simvastatin being cost‐effective for willingness‐to‐pay thresholds of £20 000 and £30 000 is 86% and 83%, respectively. Conclusions Identifying men with ED provides an opportunity to modify future cardiovascular risk and to improve MED‐QoL by treating them with 40 mg of simvastatin. The joint analysis of costs and QALY benefits suggests that there is high probability that simvastatin is a cost‐effective strategy in men with ED. The findings could influence urological and primary care practice by including questions on ED during routine consultations and relevant clinical protocols. This provides an opportunity to impart lifestyle advice.